Perceptions of psychosocial risk at work: an experience with non-professional employees at UNLP - Cassini, Julieta (2015)
“Psychosocial risks at work: analysis of their impact on the health of employees, organizations, health systems and social security” is a research project that is approved by the SECyT-UNLP. It takes place since 2014 at the Faculty of Economics of UNLP. The research team is an interdisciplinary group of professionals and university students from different field such as economics, psychology, sociology, medicine and social work. From this perspective, the aim is to reach an integrated and holistic view of the Psychosocial Risks at Work (PSRW). The study of PSRW is very important due to the impact of them in the development of the organizations, working conditions, life of workers and, its inherent financial cost of health system and social security. The main objective of this project is to explore, identify and describe perceptions of the PSRW which occur among non-professional employees at UNLP and the manifestations of health-illness process in workers and their psychological strategies to face them. Finally, it is expected to analyze the consequences of the PSRW in socioeconomic dimensions of the organizations as well.